The Concept of Maqāṣid al-Sharī'ah in the Digital Economy: A Normative Analysis of Online Transaction Practices from the Perspective of Fiqh al-Mu'āmalāt - Rizali, Muhammad; Hafidzi, Anwar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of the digital economy has significantly transformed patterns of commercial transactions in modern society, particularly through online platforms and electronic marketplaces. These developments raise important legal and ethical questions regarding the conformity of digital transactions with Islamic economic principles. This study aims to analyze the concept of Maqāṣid al-Sharī‘ah in evaluating contemporary online transaction practices within the framework of fiqh al-mu‘āmalāt. The research employs a normative legal approach based on library research by examining classical and contemporary Islamic legal literature, Qur’anic verses, hadith, and scholarly opinions related to Islamic commercial jurisprudence, as well as relevant contemporary discussions on digital economic practices. The study focuses on the application of the fundamental objectives of Islamic law, namely the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl), in assessing the legitimacy and ethical standards of online transactions. The findings indicate that online commercial activities can be considered permissible within Islamic law provided that they uphold the principles of transparency, mutual consent, fairness, and the avoidance of prohibited elements such as riba, gharar, and fraud. Furthermore, the framework of Maqāṣid al-Sharī‘ah offers a comprehensive normative foundation for evaluating emerging digital economic practices while ensuring that technological innovation remains aligned with the broader objectives of Islamic law. This study contributes to the ongoing discourse on Islamic economic jurisprudence by providing a